1978
DOI: 10.1098/rsta.1978.0082
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric chemistry: response to human influence

Abstract: Present understanding of global atmospheric chemistry is reviewed. Models are presented and compared with a wide range of atmospheric observations, with emphasis on the stratosphere. In general, excellent agreement is found between the calculated and observed distributions of long lived trace gases. The abundances of many shorter lived species are also satisfactorily reproduced, including NO 2 , HNO 3 , O, O 3 , OH and ClO. Discrepancies b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(46 citation statements)
references
References 55 publications
(75 reference statements)
2
43
1
Order By: Relevance
“…Reaction (2a) is the major source of odd nitrogen (NO x ) in the stratosphere and plays a fundamental role in regulating the ozone layer [McElroy and McConnell, 1971;Crutzen, 1971;Nicolet and Vergison, 1971;Logan et al, 1978;Wennberg et al, 1994]. Note that a consequence of the above reactions is that the mixing ratio of N 2 O in the stratosphere is depleted relative to that in the troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction (2a) is the major source of odd nitrogen (NO x ) in the stratosphere and plays a fundamental role in regulating the ozone layer [McElroy and McConnell, 1971;Crutzen, 1971;Nicolet and Vergison, 1971;Logan et al, 1978;Wennberg et al, 1994]. Note that a consequence of the above reactions is that the mixing ratio of N 2 O in the stratosphere is depleted relative to that in the troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, efforts to understand the future impact of continued usage of chlorofluoromethanes (CFM), CH3CC13, and of nitrous oxide have broadened in scope to consider the coupled effects of increasing atmospheric CO2 and CFM concentrations [Luther eta [Weiss, 1981]. Further, Logan et al [1978] demonstrated the potential effects of combustion-produced gases on tropospheric 03 and OH and through these OH changes, the effects on stratospheric chlorine and ozone concentrations. The more speculative but plausible increases in tropospheric ozone due to commercial aircraft operations [Liu eta!., 1980;Derwent, 1982] would necessitate a still broader view of atmospheric ozone perturbations, especially from the point of view of trend assessment in ground-based total ozonecolumn measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Stratospheric chemistry has been reviewed extensively by several authors (Nicolet, 1975;Johnston and Pokolske, 1978;Logan et al, 1978;Thrush, 1978). An excellent summary of information available up to the mid-1979 is given by NASA (1979).…”
Section: Review Of Atmospheric Chemistrymentioning
confidence: 99%